2014
DOI: 10.1128/ec.00260-13
|View full text |Cite
|
Sign up to set email alerts
|

TbKAP6, a Mitochondrial HMG Box-Containing Protein in Trypanosoma brucei, Is the First Trypanosomatid Kinetoplast-Associated Protein Essential for Kinetoplast DNA Replication and Maintenance

Abstract: Kinetoplast DNA (kDNA), the mitochondrial genome of trypanosomatids, is a giant planar network of catenated minicircles and maxicircles. In vivo kDNA is organized as a highly condensed nucleoprotein disk. So far, in Trypanosoma brucei, proteins involved in the maintenance of the kDNA condensed structure remain poorly characterized. In Crithidia fasciculata, some small basic histone H1-like kinetoplast-associated proteins (CfKAP) have been shown to condense isolated kDNA networks in vitro. High-mobility group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…In the tripanosomids Crithidia fasciculata and Trypanosoma cruzi , histone H1‐like proteins are associated with the kinetoplast DNA (Xu et al ., ; de Souza et al ., ), while a proteomic study of the Trypanosma brucei kinetoplast failed to identify any HMG proteins, but revealed, as associated with DNA a protein with no homologues outside trypanosomes (Beck et al ., ). However and in contradiction with the above, a very recent article, describes TbKAP6, an HMG‐box protein of T. brucei associated with the kinetoplast and essential for viability (Wang et al ., ). The process of ‘evolutionary tinkering’ by which proteins of different evolutionary origins are recruited into mitochondrial nucleoids has been discussed by Kucej and Butow ().…”
Section: Discussionmentioning
confidence: 97%
“…In the tripanosomids Crithidia fasciculata and Trypanosoma cruzi , histone H1‐like proteins are associated with the kinetoplast DNA (Xu et al ., ; de Souza et al ., ), while a proteomic study of the Trypanosma brucei kinetoplast failed to identify any HMG proteins, but revealed, as associated with DNA a protein with no homologues outside trypanosomes (Beck et al ., ). However and in contradiction with the above, a very recent article, describes TbKAP6, an HMG‐box protein of T. brucei associated with the kinetoplast and essential for viability (Wang et al ., ). The process of ‘evolutionary tinkering’ by which proteins of different evolutionary origins are recruited into mitochondrial nucleoids has been discussed by Kucej and Butow ().…”
Section: Discussionmentioning
confidence: 97%
“…The repair polymerase PolIA, which is mostly localized in the mitochondrial matrix was not detected. Surprisingly we also found several proteins that have been described to be localized inside the kDNA disc including the gap repair polymerase POL beta PAK and the HMG-box containing proteins KAP3, KAP4 and KAP6 that are thought to fulfill the role of histone proteins in the kDNA (Wang et al, 2014;Xu et al, 1996). Also the third compartment, the antipodal sites, seem to be linked to the TAC even without the kDNA being present.…”
Section: Discussionmentioning
confidence: 61%
“…Most prominently the kDNA associated proteins KAP3, KAP4 and KAP6. KAP3 was described as a histone H1 like protein in Crithidia fasciculata, while KAP6 is a HMG box containing protein described in T. brucei (Wang et al, 2014;Xu et al, 1996). Bloodstream form trypanosomes have a metabolically much reduced mitochondrion and mutants can be selected that are able to live without a mitochondrial genome.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that certain DNA minor groove binding compounds were able to enter the mitochondrion of Trypanosoma brucei, bind to AT sequences of kDNA and, as a result, cause cell death (60). It was suggested that these minor groove binding compounds may disrupt the functions of kDNA binding proteins, such as the TbKAP6 protein that is essential for kDNA replication and maintenance and also for cell viability (61). TbKAP6 contains two HMG boxes and binds to DNA minor groove (61).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that these minor groove binding compounds may disrupt the functions of kDNA binding proteins, such as the TbKAP6 protein that is essential for kDNA replication and maintenance and also for cell viability (61). TbKAP6 contains two HMG boxes and binds to DNA minor groove (61).…”
Section: Discussionmentioning
confidence: 99%